Vannier: La sociologie en toutes lettres - Rocquin, Baudry (Serendipities. Journal for the Sociology and History of the Social Sciences, 2021)
Book review of: Vannier, Patricia (Ed.) (2019) La sociologie en toutes lettres: L’histoire de la discipline à travers les correspondances. Toulouse: Presses Universitaires du Midi 284 pp. ISBN: 978-2810706228 Price: €23,00